Chromosome-scale haploid genome assembly of Durio zibethinus KanYao - Xiaohao Ji; Yiwang Zhong; Daojun Zheng; Shenghua Xie; Meng Shi; Xiaodi Wang; Fengzhi Liu; Xuejie Feng; Haibo Wang (Scientific Data)
Abstract Durian (Durio zibethinus) is a tropical fruit valued for its nutritional and commercial significance. In this study, we generated two high-quality, haplotype-resolved, chromosome-level genomes of the durian cultivar ‘Kan Yao’, each with 28 chromosomes. The total genome lengths were 737.2 Mb and 763.8 Mb, with contig N50 values of 22.9 Mb and 21.5 Mb, and scaffold N50 values of 25.9 Mb and 26.7 Mb, respectively. Nineteen chromosomes were assembled without gaps, while the remaining nine contained 1 to 10 gaps. Genome annotation identified 53,125 and 53,101 functional genes, as well as 5,254 and 5,496 non-coding RNAs. The high-quality assembled genomes will aid in the molecular breeding of durian.